(untitled) (Journal of Chemical Engineering, 2013)
The potential of recycled waste polymeric materials as a substitute for aggregates in concrete has been investigated in the study. Two different types of waste polymer, namely polyurethane formaldehyde (PUF) based packaging waste and high density polyethylene (HDPE) were recycled and used in the experiment. Concrete and masonry poly block specimens were prepared using recycled polymer materials, and test specimens were characterized. The effects of waste polymer materials on the mechanical, physical and morphological properties of concrete and poly blocks have been investigated. The result shows that the inclusion of waste polymer materials decreases density, porosity and water absorption of concrete and poly blocks significantly. Polyurethane formaldehyde (PUF) based block exhibited lower density than that of HDPE-based concrete. Due to exceptionally low density, recycled polymer modified blocks and concrete can be used in non-load bearing structures, floating structures and where light weight materials recommended. DOI: http://dx.doi.org/10.3329/jce.v27i1.15859 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 53-57